Role of Staple Food Fortification in Combating Micronutrient Deficiency - Abraham, Sindhu; Furtado, Sharon; SN, Amruthavarshini; C, Suman (Indian Journal of Pharmaceutical Education and Research, 2026)
Micronutrient deficiencies, often referred to as “hidden hunger,” result from a dearth of vital nutrients and minerals in the diet, causing malnutrition. The mortality rate of children under the age of five is high in India, with more than half of these deaths linked to deficiencies in iron, zinc, iodine, and folic acid. During pregnancy and lactation, elevated levels of calcium and other essential minerals in the bloodstream are required to ensure adequate nutrition. Should the dietary intake of calcium fall short of meeting this increased demand, it could jeopardize the health of both the mother and child. Fortification has emerged as an established, cost-effective, and sustainable method for delivering vital nutrients to a large population and involves an intentional increase in the content of specific vitamins and minerals in staple foods or food products to boost their nutritional quality. This not only prevents deficiencies but also restores nutrients that may be lost during food processing, contributing to improved public health outcomes with minimal risks. This review highlights the importance of fortifying staple foods with micronutrients to improve nutrient absorption. Regular consumption of these food products ensures a steady supply of micronutrients, thus improving overall health.
Keywords: Fortification; Malnutrition; Micronutrients; Staple food